Design and manufacture of hollow fiber module gas separator - Saidi, Hamdani; Abdul Aziz, Ramlan; Hassan, H.; Ariffin, A. (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
Hollow fiber cellulose acetate membranes with asymmetric structure were prepared using a wet spinning method. In the preparation procedures, spinning parameter(i.e bore liquid flowrate) has been identified to influence the shape and the hollow fiber thickness. Spinneret dimension also influences the hollow fiber thickness produced. The membrane structures are characterised by using Scanning Electron Microscope. In this study hollow fiber membranes with an asymmetric structure were manufactured using a locally-designed spinneret. This paper also discusses the development of the hollow fiber membrane module.